Controls of hydrothermal fluid flow and gold mineralization in the Twin Hills deposit and adjoining areas, Central Zone, Damara Belt - Shilunga, Josia Tulongeni (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2024.